Pengembangan Aplikasi Kuliah Kerja Nyata Pada IAIN Salatiga Dengan Metode Prototype - Agung Suprapto (Faculty of Computer Science, University of Jember, 2020)
During this time the management process of managing Kuliah Kerja Nyata at IAIN Salatiga still uses the conventional way by involving documents manually so it takes a long time. The purpose of this study is to build applications that are useful for handling the process of managing Kuliah Kerja Nyata (KKN) at IAIN Salatiga starting from registering data management, KKN supervisor lecturer management, to reporting the results of KKN. The application development method used in this study is the prototype method and in testing its application using the BlackBox testing method. From the results of the Blackbox, The Testing test shows that the application of a Kuliah Kerja Nyata on the Salatiga IAIN as a whole the functionality can run well.